2019
DOI: 10.1248/bpb.b18-00728
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Pharmacological Profile of Ipragliflozin, a Sodium Glucose Co-transporter 2 Inhibitor

Abstract: Ipragliflozin, a selective sodium glucose cotransporter 2 (SGLT2) inhibitor, is used for the treatment of type 2 diabetes mellitus. To date, the only known in vitro pharmacological characteristic of ipragliflozin is its selectivity for SGLT2 over SGLT1, which was previously reported by our group. Therefore, in this study, we investigated other in vitro pharmacological characteristics of ipragliflozin and compared them with those of phlorizin, a naturally occurring SGLT inhibitor. Selectivity of ipragliflozin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The mode of inhibition of DWP16001 was not different from the other SGLT2 inhibitors. They all showed reversible and competitive inhibition ( Figure 10), which is consistent with other SGLT2 inhibitors [23,24]. However, the affinity to SGLT2 inhibition seemed to be different among the three SGLT2 inhibitors ( Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…The mode of inhibition of DWP16001 was not different from the other SGLT2 inhibitors. They all showed reversible and competitive inhibition ( Figure 10), which is consistent with other SGLT2 inhibitors [23,24]. However, the affinity to SGLT2 inhibition seemed to be different among the three SGLT2 inhibitors ( Table 3).…”
Section: Discussionsupporting
confidence: 81%
“…Ipragliflozin is being used as a treatment for T2DM either alone or as an add-on to various other anti-hyperglycemic agents such as metformin (sulfonylurea), DPP-4 inhibitors or nateglinide (α-glucosidase inhibitor) and pioglitazone. 69,70 25 and 50 mg tablets of ipragliflozin have been approved, administered as a dose of 50 mg per day either before or after breakfast. The ipragliflozin dose can be increased up to 100 mg per day if 50 mg is found to be insufficient.…”
Section: Sglt Inhibitorsmentioning
confidence: 99%
“…Very recently, in December 2018, Astellas Pharma and Kotobuki pharmaceutical Co. Ltd. got approval for Suglat for the additional indication of T1DM in Japan. 69,70 After in vitro pharmacological studies, ipragliflozin was found to inhibit SGLT2 competitively and also have high selectivity for SGLT2 over other members of the SGLT family. 69 …”
Section: Sglt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It inhibits SGLT-2 from the tubular side in a competitive manner. Due to the structural formula and high SGLT-2 selectivity, SGLT-2i can only act at the proximal tubule at clinical pharmacological concentrations [13]. From various studies, SGLT-2i can cause not only urinary glucose excretion but also several suppressive actions on the cardiovascular event including the effect of lowering blood pressure.…”
mentioning
confidence: 99%